Culture-sensitive and standard pain neuroscience education improves pain, disability, and pain cognitions in first-generation Turkish migrants with chronic low back pain: a pilot randomized controlled trial. (4th May 2021) - Orhan, Ceren; Lenoir, Dorine; Favoreel, An; Van Looveren, Eveline; Yildiz Kabak, Vesile; Mukhtar, Naziru Bashir; Cagnie, Barbara; Meeus, Mira
ABSTRACT: Purpose : To compare the effectiveness of culture-sensitive and standard pain neuroscience education (PNE) on pain knowledge, pain intensity, disability, and pain cognitions in first-generation Turkish migrants with chronic low back pain (CLBP). Methods : Twenty-nine Turkish first-generation migrants with CLBP were randomly assigned to the culture-sensitive (n = 15) or standard PNE (n = 14) groups. Primary (pain knowledge, pain intensity, and disability) and secondary outcomes (pain beliefs, catastrophization, and fear of movement) were evaluated at baseline, immediately after the second session of PNE (week 1), and after 4 weeks. Results : There was a significant main effect of time in pain knowledge ( p < .001), pain intensity ( p = .03), disability ( p = .002), organic and psychological pain beliefs ( p = .002, p = .01), catastrophization ( p = .002), and fear of movement ( p = .02). However, no significant difference was found between groups in terms of all outcome measures ( p > .05). Conclusions : Both PNE programs resulted in improvements in knowledge of pain, pain intensity, perceived disability, and pain cognitions. Nevertheless, the superiority of the culture-sensitive PNE approach could not be proved. Therefore, maybe migrants who are living in the host country for longer length of time do not need culturally adapted therapies due to cultural integration, while these adaptations might be essential for the recent migrants or the autochthonous population in Turkey. Further research is required to investigate the effects of culture-sensitive PNE alone or in combination with physiotherapy interventions in recent migrants or Turkish natives with CLBP.